ESTIMACIÓN DE LA CUBIERTA DE NIEVE EN EL NORTE DE LA PROVINCIA DEL NEUQUÉN - Marisa Cogliati; Damian Groch; Florencia Finessi (Boletín Geográfico)
The snow and ice cover analysis in mountainous terrain is an important information for hydrology, and can be obtained from remote sensors. Determining snow area is particularly important during spring and summer in mountainous land where, snow can be melted quickly causing large spatial variations in the mixed cover of snow, vegetation and soil. This paper present the utilization of a binary method for the calculation of the snow covered area in the Andes, in the northern of the Neuquén province using LANDSAT imagery and MOD10A1 MODIS products for two satellite scenes one summer scene and a winter one both from year 2000. The LANDSAT scene was used as validation because of its greater spatial resolution. The subscenes were chosen selecting images free of cloudiness. The validation of these methods is in continuous development, though the utilization of LANDSAT images is an imperfect source of validation this improves the results of MODIS sensor offering information with 30 m of spatial resolution. In LANDSAT imagery the snow covered area was calculated with NDSI less than 0.4 values and NDVI values above 0.1 simultaneously with surface temperature below 277 K. Snow cover maps were obtained for both scenes for different months, including Wind Chain the northern of Neuquén province, one scene in august (winter) and the other in spring time. The results indicate differences in the estimation of the snowfall area related to season and the spatial resolution of data.